2018
DOI: 10.5539/elt.v11n2p156
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Pre-service EFL Teachers’ Self-concepts within the Framework of Teaching Practicum in Turkish Context

Abstract: The present study aimed at understanding the nature and potential dynamism of five pre-service EFL teachers' self-concepts in the domain of English as a foreign language (EFL). To this end, the effects of pre-service teachers' experiences gained alongside the practicum on their EFL self-concept development were also discussed. Data were generated in a case study research paradigm using journal entries and in-depth interviews. The major themes derived from the analysis of the data were indicative of pre-service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition, research by Barkhuizen and Feryok (2006); Ward and Ward (2003) and Willard-Holt (2001) found that teaching practicum improves pre-service teachers' professional competence. Yilmaz (2018) also conducted research in the Turkish context in regard with the benefit of teaching practicum. The finding of the study suggests that preservice teachers develop their self-concept as the result of their participation in the practicum program.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research by Barkhuizen and Feryok (2006); Ward and Ward (2003) and Willard-Holt (2001) found that teaching practicum improves pre-service teachers' professional competence. Yilmaz (2018) also conducted research in the Turkish context in regard with the benefit of teaching practicum. The finding of the study suggests that preservice teachers develop their self-concept as the result of their participation in the practicum program.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the research paradigm employed in the previous studies mentioned above, especially about teacher and preservice teacher selfconcept, most of the above-mentioned studies were done quantitatively and only a few studies were done in the qualitative paradigm. To name a few, only research was done by Alagozlu (2016); Dobbins (1996); Rachmawati et al (2017); Yilmaz (2018) which used a qualitative approach. Furthermore, only the studies conducted by Alagozlu (2016); Rachmawati et al (2017); Yilmaz (2018) focused on EFL preservice teacher self-concept.…”
Section: Figure 1 Self-concept Of Teachermentioning
confidence: 99%
“…To name a few, only research was done by Alagozlu (2016); Dobbins (1996); Rachmawati et al (2017); Yilmaz (2018) which used a qualitative approach. Furthermore, only the studies conducted by Alagozlu (2016); Rachmawati et al (2017); Yilmaz (2018) focused on EFL preservice teacher self-concept. Alagozlu's (2016) study was concerned with the professional selfconcept of EFL teachers.…”
Section: Figure 1 Self-concept Of Teachermentioning
confidence: 99%
See 2 more Smart Citations